2022
DOI: 10.1101/2022.08.11.503542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A common mechanism of Sec61 translocon inhibition by small molecules

Abstract: The Sec61 complex forms a protein-conducting channel in the endoplasmic reticulum (ER) membrane that is required for secretion of soluble proteins and production of many membrane proteins. Several natural and synthetic small molecules specifically inhibit the Sec61 channel, generating cellular effects that are potentially useful for therapeutic purposes, but their inhibitory mechanisms remain unclear. Here we present near-atomic-resolution structures of the human Sec61 channel inhibited by a comprehensive pane… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Our work now suggests that alterations to the ER membrane may also impact Sec61-mediated protein insertion and highlights the importance of understanding the localized membrane effects resulting from Sec61 cofactor association. Further, different natural and synthetic small molecule inhibitors of Sec61 are accommodated within Sec61 in subtly different open conformations (Rehan et al 2022); (Itskanov et al 2022) and detailed understanding of Sec61 conformational control by the surrounding lipid and protein environment will be important for targeting Sec61 with therapeutic small molecules. Further structural and mechanistic work is required to understand a possible direct role that TRAP may have in directing protein N-glycosylation with OST.…”
Section: Discussionmentioning
confidence: 99%
“…Our work now suggests that alterations to the ER membrane may also impact Sec61-mediated protein insertion and highlights the importance of understanding the localized membrane effects resulting from Sec61 cofactor association. Further, different natural and synthetic small molecule inhibitors of Sec61 are accommodated within Sec61 in subtly different open conformations (Rehan et al 2022); (Itskanov et al 2022) and detailed understanding of Sec61 conformational control by the surrounding lipid and protein environment will be important for targeting Sec61 with therapeutic small molecules. Further structural and mechanistic work is required to understand a possible direct role that TRAP may have in directing protein N-glycosylation with OST.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our lead CADA compound that has different side groups compared to CK147 (Fig. 3A) presumably binds to the site weakly and the binding is reversible (38,50,51). This interplay between the inhibitor and SP binding could define the client specificity and selectivity for translocon inhibitors.…”
Section: Discussionmentioning
confidence: 98%
“…A recent cryo-EM study of the Sec61 translocon exposed to a novel cotransin analog, KZR-8445 containing a large cyclic heptadepsipeptide ring, reveals binding of the inhibitor to the SPbinding cleft (53). Another recent Sec61 structural study of multiple translocation inhibitors, including mycolactone and CADA, showed an overlapping binding site near the lateral gate of Sec61 for all the inhibitors (50). The presented cryo-EM structures, however, were of a post-translocational human/yeast chimeric complex of Sec61/Sec63/Sec71/Sec72 (50), and the compounds were soaked at significantly high compound concentrations.…”
Section: Different Inhibitor Binding Sites In Sec61mentioning
confidence: 99%
“… 16 We could show that ES24 indeed inhibits Sec-dependent protein translocation in both Gram-negative and Gram-positive bacteria. Given recent structural evidence that ES1 intercalates in the lateral gate/plug region of the Sec61 secretion system, thus blocking the translocation channel, 14 it is reasonable to assume that ES24 may bind similarly to the homologous bacterial SecYEG channel. Additionally, ES24 induces DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“… 11 − 13 Recently, a cryogenic electron microscopy (cryo-EM) structure of Sec61 in complex with ES1 has been solved. 14 ES24 is a smaller derivative of ES1, which retains its activity against Sec61 but not the ERAD system. 11 Since the eukaryotic Sec61 complex is homologous to the bacterial SecYEG translocon, 15 ES1 and ES24 have also sparked interest as potential inhibitors of bacterial protein secretion, a pathway that is essential in both Gram-positive and Gram-negative bacteria but has not yet been exploited as an antibiotic target.…”
mentioning
confidence: 99%